Rural banking and agricultural financing- A case study of Kwamanman Rural Bank Ltd - Gyabea, Hannah (2016)
A Thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the degree of Master of Business Administration (Finance Option).